Which features of psychopathy and impulsivity matter most for prison violence? New evidence among female prisoners. (May 2019) - Thomson, Nicholas D.; Vassileva, Jasmin; Kiehl, Kent A.; Reidy, Dennis; Aboutanos, Michel; McDougle, Robyn; DeLisi, Matt
Abstract: Prison violence is a complex and multifaceted phenomenon. While a great deal of research has been conducted in male samples, very few studies are dedicated to understanding violence committed by female offenders. Two constructs that have emerged as important predictors of violence are psychopathy and impulsivity. These constructs may be an important line of inquiry due to the close association between psychopathy, impulsivity, and violence. In a sample of 166 female offenders, we used the 3-facet model of psychopathy and 3-factor model of trait impulsivity with the goal to statistically explain two types of prison violence: official reports of violent misconducts over a 12-month period, and self-report of deliberately instigating a violent altercation. We conducted three separate regression models to test the independent contribution of psychopathy and impulsivity, as well as accounting for the overlap between psychopathy and impulsivity. When impulsivity and psychopathy were not competing within the same model, affective and behavioral psychopathic traits, and nonplanning impulsiveness predicted violent misconducts. However, when accounting for impulsivity and psychopathy within the same model, only affective psychopathic traits remained significant. When predicting if an offender deliberately started a violent altercation, separate statistical models showed affective and interpersonal psychopathic traits, and nonplanning impulsiveness were significant. When competing for variance within the same statistical model, only affective and interpersonal psychopathic traits remained as significant predictors. This suggests an overlap between psychopathic traits and nonplanning impulsivity when understanding violent misconducts in female offenders, while affective psychopathic explains female prison violence, regardless of impulsivity.